Обеспечение добросовестности научных исследований: опыт университетов США - Сбруев, Николай (Studies in Comparative Education, 2014)
В статье рассмотрены проблемы этической регламентации исследовательской деятельности в университетах США; определены цели и задачи кодексов и руководств по этике научных исследований; охарактеризованы основные аспекты деятельности администратора исследований по обеспечению научной добросовестности. The article deals with the following: the ethical regulation of research at U.S. universities, goals and objectives of codes and guidelines on research ethics, highlights of the research administrator activities to ensure research integrity. At present world scientific community stresses the issue of research ethical conduct importance. During recent decades plenty of world`s leading universities and US universities in particular establish and imply codes of research and educational ethics. Despite a variety of forms and sets of basic regulations and peculiarity of universities’ and professional communities’ scientific interest orientation, all of them are, to different extent, aiming at research integrity enhancement. Such research administration issues as authorship affiliation and attribution, order of the authors in a publication, double publications, data and research results management should be settled at the institutional level with regard for specificity of a certain research area. A significant role in the process of solving the problems mentioned above is given to research administration offices. A scientific research is an interactive process carried out by people who have their own strivings and ambitions. A conflict while conducting a research is aroused by inevitability of contradictions between the researcher`s personal interest, his/her objective of their own ideas` advancing and the aim of a research group and its other members. The society’s level of confidence in science to a significant extent depends on maintaining high ethical standards in research by the researchers themselves as well as university research administrations. Following the given principles will help the researcher to avoid deviation from accepted ethical norms, thus preventing serious violations in researcher’s professional conduct which lead to misconducts resulting in a research devoid of integrity. The attempt at dwelling upon certain ethical aspects of US universities research administrators’ activity made in the paper can be of use to Ukrainian researchers as a guideline to common American practices and serve as a sample for those starting their scientific carrier.